2023
DOI: 10.1200/jco.22.01503
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Survival Outcomes With Nivolumab Plus Ipilimumab Versus Chemotherapy as First-Line Treatment for Metastatic Non–Small-Cell Lung Cancer in CheckMate 227

Abstract: PURPOSE We present 5-year results from CheckMate 227 Part 1, in which nivolumab plus ipilimumab improved overall survival (OS) versus chemotherapy in patients with metastatic non-small cell lung cancer (mNSCLC), regardless of tumor programmed death ligand 1 (PD-L1) status. METHODS Adults with stage IV/recurrent NSCLC without EGFR mutations or ALK alterations and with tumor PD-L1 ≥1% or <1% (N=1739) were randomized. Patients with tumor PD-L1 ≥1% were randomized to first-line nivolumab plus ipilimumab, nivolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
91
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(118 citation statements)
references
References 26 publications
3
91
0
Order By: Relevance
“…In addition, especially in the population with PD-L1<1%, the efficacy of NIVO+IPI combined regimen was superior to that of NIVO / IPI+chemotherapy in all aspects. 40 Therefore, these results also indicated that PD-L1 expression could not be a single indicator for predicting the efficacy of dual immunotherapy. For patients treated with bsAbs, it is more important to accurately identify biomarkers in the exclusion of ITH, rather than just using the traditional detection technique.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, especially in the population with PD-L1<1%, the efficacy of NIVO+IPI combined regimen was superior to that of NIVO / IPI+chemotherapy in all aspects. 40 Therefore, these results also indicated that PD-L1 expression could not be a single indicator for predicting the efficacy of dual immunotherapy. For patients treated with bsAbs, it is more important to accurately identify biomarkers in the exclusion of ITH, rather than just using the traditional detection technique.…”
Section: Discussionmentioning
confidence: 95%
“…However, in the recently published Checkmate 227 update reporting the 5-year clinical outcomes of the trial, comparing first-line immunotherapy combination to chemotherapy in metastatic NSCLC, immunotherapy achieved substantial long-term clinical benefit regardless of PD-L1 expression. The 5-year OS rates in PD-L1 negative (<1%) patients were 19% (nivolumab plus ipilimumab) versus 7% (chemotherapy), which might lead to revisiting the actual clinical impact of this parameter [ 36 ]. Additionally, we have considered responders as any patient who had not progressed at 6 months, but we did not differentiate the different types of response in our models.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent clinical studies established the effectiveness of PD-1 blockade plus an anti-cytotoxic T-lymphocyte-associated antigen 4 (CTLA4) antibody as a rst-line treatment for advanced NSCLC [2][3][4] and malignant melanoma [5]. In particular, the combination of the nivolumab (Nivo) and the anti-CTLA4 antibody ipilimumab (Ipi) provided long-term survival (5-year survival rate: approximately 20%), even in NSCLC patients with PD-LI negativity [2]. However, the therapeutic biomarkers for anti-CTLA4 antibody e cacy remain unclear.…”
Section: Introductionmentioning
confidence: 99%